No colo da ama de leite: a prática cultural da amamentação e dos cuidados das crianças na Província do Grão-Pará no século XIX - GUTIERRES, Damiana Valente Guimarães (Universidade Federal do Pará, 2013)
The present study deals with the cultural practice of breastfeeding and care of children by wet nurses in the Province of Grão-Pará in the nineteenth century. The wet nurses had an important role in the symbolic, social and cultural life of the private patriarchal society-slavery in Brazil in the nineteenth century. In the Province of Grão-Pará was recurrent hiring wet nurses to breastfeed and care for children. The central question that guided the study was: What is the presence of wet nurses in the childhood history of Pará, especially the cultural meanings, social and emotional life of the child in the Province of Grão-Pará in the nineteenth century? The research objectives were: a) identify the source of wet nurses and their importance to the history of childhood, b) describe the history of breastfeeding and speeches health doctors on the care of the child, the mother and the love of milk c) highlight the significance of wet nurses in nursing, care and education of children in the nineteenth century in the Province of Grão-Pará d) identify the request the services of wet nurses to meet the children in the Province of Grão Para. Methodologically use historical research and documentation, consisting of a corpus of 92 ads published in the period 1845-1888, in newspapers paraenses May Thirteen, The Constitution, Diary of Belém, Pará The Liberal, Regeneration, Official Gazette, Gazette The commerce and Pará. The corpus was obtained from the Library Arthur Vianna (CENTUR) and the National Digital Library Newspaper Library, having been organized in 12 categories of analysis, based on content analysis Laurence Bardin. The results demonstrate the existence of a trade indiscriminate sale of wet nurses in the Province of Grão-Pará, including valuing the younger, with good manners, good hygiene, healthy and had not created. The social profile of the wet nurses of the Province of Grão-Pará during the study period was similar to those present in the other provinces of Brazil, and it was usually a slave and free, was poor and predominantly black. In the late nineteenth century, doctors hygienists argued that wet nurses transmitted diseases and were "mercenary", recommending breastfeeding or using formula milk. However, it was found that the influence of wet nurse for the child was beyond the affective relationship, reflecting on their education, language, food, short in several aspects of their culture.